Handbook of Vinyl Formulating. - Grossman, Richard F. (Wiley series on plastics engineering and technology., 2008)
Here is your starting point and complete guide to polyvinyl chloride (PVC) formulation. It covers the basics of vinyl formulation, starting formulations for compounds, and the latest compounding ingredients. Since publication of the acclaimed first edition, a standard reference used by vinyl technologists around the world, there have been many new developments in vinyl formulation as well as new discoveries and insights into the underlying mechanisms. It's all covered here in the second edition, in one highly readable, expertly organized volume.